Research on Application of SR Protection Technology in 5G eMBB Scenarios - Hao ZHANG; Guo-hui LIU; Xin-quan ZHANG (Guangtongxin yanjiu, 2022)
As the traditional 4th Generation Mobile Communication (4G) bearer network can only meet the 2G, 3G and 4G wireless service backhaul bearer, it cannot meet the higher requirements of 5G wireless backhaul on the bearer network in terms of bandwidth, delay, slicing, and reliability. It also cannot satisfy the extremely demanding real-time protection switching requirements in various 5G service scenarios, as well as the service protection and fast convergence requirements in the enhanced Mobile Broadband (eMBB) scenario. In order to solve this issue, the article proposes a Segmented Routing (SR) tunnel technology in the 5G bearer network protection application scheme. This scheme adopts the connection-oriented SR-Transport Profile (SR-TP) tunnel enhancement technology for the end-to-end protection application of the north-south services in the 5G bearer network, and the optimal SR-Best Effort (SR-BE) tunnel technology for the east-west direction protection applications for connectionless services. Experimental results show that, compared with the traditional 4G bearer network protection scheme, it can fully solve the various requirements of the 5G eMBB service scenario for the bearer network. The service protection switching is completed within 50 ms, which can fully meet the carrier-level protection switching requirements.